Walking with the spectrum: A phenomenological study on the experiences of mothers raising an Autistic child - Navira Ali Akhai; Mudassar Aziz; Gulnaz Anjum (JISR Management and Social Sciences & Economics, 2022)
The purpose of this study was to explore the experiences of the mothers raising an autistic child, the struggles they faced, the misconceptions they had, the factors that altered their mental framework in effectively managing their child and their condition. 7 Detailed semi structured interviews of mothers raising a child with autism, were conducted to develop a better understanding of their situation and the factors that affected them. A phenomenological methodology was used to uncover the lived experiences of these mothers. Results revealed the existence of 7 distinct themes that provided insight into the real experience of a mother raising a child with autism. Themes focused on the mothers mental frameworks, which included denial of red flags, mother-researcher, emotional paradox, cognitive processing, indicating the thought patterns and emotional processes the mother used in dealing with her child. Moreover themes such as Family dynamics, Societal micro-aggression, medical resistance, the unspoken bond and redefining inclusion were noted for a comprehensive understanding of the experience of raising a child with Autism. The results revealed that although it seems like it is a topic well known, mothers still lack the awareness to detect signs of autism and to manage them effectively, health professionals and families need to work in collaboration to uplift the mother and child from chronic periods of distress.